2009
DOI: 10.1089/hum.2009.031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adeno-Associated Virus Serotype and Genomic Structure on Liver Transduction and Biodistribution in Mice of Both Genders

Abstract: Recombinant adeno-associated viral (AAV) vectors have unique properties, which make them suitable vectors for gene transfer. Here we assess the liver transduction efficiency and biodistribution of AAV-pseudotyped capsids (serotypes) 1, 5, 6, and 8, combined with single-stranded and double-stranded genomic AAV2 structures carrying the luciferase reporter gene after systemic administration. The analysis was performed in vivo and ex vivo, in male and female mice. Gender-related differences in AAV-mediated transdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
82
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 44 publications
6
82
1
Order By: Relevance
“…Besides mouse strain, animal gender has also been shown to influence rAAV-mediated gene delivery, transgene expression and biodistribution. 27,28 In a study addressing liver-directed delivery of vector particles, Davidoff et al 27 reported 5-to 13-fold higher transgene expression in male compared with female mice, irrespective of the promoter, cDNA and mouse strain. Moreover, molecular analysis revealed that the rAAV genome was stably retained in male liver at levels that were sevenfold higher than those observed in females.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides mouse strain, animal gender has also been shown to influence rAAV-mediated gene delivery, transgene expression and biodistribution. 27,28 In a study addressing liver-directed delivery of vector particles, Davidoff et al 27 reported 5-to 13-fold higher transgene expression in male compared with female mice, irrespective of the promoter, cDNA and mouse strain. Moreover, molecular analysis revealed that the rAAV genome was stably retained in male liver at levels that were sevenfold higher than those observed in females.…”
Section: Discussionmentioning
confidence: 99%
“…These differences were observed with both rAAV2-and rAAV5-based vectors. In a relatively recent study, Paneda et al 28 reported gender-related differences in rAAV-mediated liver transduction and biodistribution for the serotypes 1, 5, 6 and 8. To the best of our knowledge, there are no prior studies comparing the effect of animal gender on AAV2/9-mediated pulmonary gene transfer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vector of choice was dsAAV1-PBGDLuc, which expresses luciferase from a ubiquitous porphobilinogen deaminase promoter (PBGD) and contains a double-stranded genome (Figure 1a). 20 We considered that transduction of AAV vectors could be different depending on the route of administration used for viral entry. Therefore, we introduced 3.4Â10 10 viral genomes of dsAAV1-PBGD-Luc through the hepatic artery (n¼6), the portal vein (n¼6) or by direct injection into the liver (n¼6).…”
Section: Analysis Of Aav Transduction In Rat Livers Before During Anmentioning
confidence: 99%
“…The clear benefit is that transduction from dsAAV is faster and 10-to 20-fold higher than transduction from standard single-stranded AAV (ssAAV). [18][19][20] Transgene expression mediated by AAVs can persist for several years in vivo. 21,22 AAV genomes persist in non-dividing cells as episomal DNAs, but a very low level of integration could also occur.…”
Section: Introductionmentioning
confidence: 99%